2015
DOI: 10.1248/bpb.b15-00086
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 1 µg/kg Dexmedetomidine Combined with High-Volume/Low-Concentration Caudal Ropivacaine in Children Undergoing Ambulatory Orchiopexy

Abstract: When local anesthetics are used, the administration of dexmedetomidine (DEX) can prolong analgesic duration. However, the effect of caudal DEX on high volume/low concentration (HVLC) local anesthetics has not been studied. We investigated the analgesic effect of DEX added to a HVLC of ropivacaine for caudal block in children. Eighty children (the American Society of Anesthesiologists (ASA) status I; age, 1-6 years) undergoing ambulatory orchiopexy were enrolled in the study. Children were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Five trials in the included studies were CCTs ( 36 , 46 , 65 , 66 , 76 ). The patients in 17 trials ( 20 , 22 , 28 30 , 32 , 39 , 43 , 49 , 50 , 52 , 54 , 61 , 64 , 72 , 74 , 78 ) underwent otolaryngology surgeries, those in 5 trials ( 36 , 44 , 66 , 67 , 70 ) underwent dental or cleft palate surgeries, those in 9 trials ( 19 , 26 , 38 , 40 , 53 , 55 – 57 , 63 ) underwent ophthalmic surgeries, those in 11 trials ( 21 , 27 , 33 , 34 , 37 , 41 , 42 , 47 , 68 , 69 , 71 ) underwent general or urological surgeries, those in 4 trials ( 23 , 31 , 62 , 73 ) underwent orthopedic surgeries, those in 1 trial ( 65 ) underwent cardiac surgery, those in 8 trials ( 24 , 45 , 46 , 58 60 , 75 , 79 ) underwent invasive examination or treatment, those in 5 trials ( 25 , 35 , 76 , 77 , 81 ) underwent non-invasive examination or treatment, and those in 3 trials ( 48 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five trials in the included studies were CCTs ( 36 , 46 , 65 , 66 , 76 ). The patients in 17 trials ( 20 , 22 , 28 30 , 32 , 39 , 43 , 49 , 50 , 52 , 54 , 61 , 64 , 72 , 74 , 78 ) underwent otolaryngology surgeries, those in 5 trials ( 36 , 44 , 66 , 67 , 70 ) underwent dental or cleft palate surgeries, those in 9 trials ( 19 , 26 , 38 , 40 , 53 , 55 – 57 , 63 ) underwent ophthalmic surgeries, those in 11 trials ( 21 , 27 , 33 , 34 , 37 , 41 , 42 , 47 , 68 , 69 , 71 ) underwent general or urological surgeries, those in 4 trials ( 23 , 31 , 62 , 73 ) underwent orthopedic surgeries, those in 1 trial ( 65 ) underwent cardiac surgery, those in 8 trials ( 24 , 45 , 46 , 58 60 , 75 , 79 ) underwent invasive examination or treatment, those in 5 trials ( 25 , 35 , 76 , 77 , 81 ) underwent non-invasive examination or treatment, and those in 3 trials ( 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Random sequence generation was assessed as a low risk of bias in 57 studies (98%), allocation concealment was assessed in 36 studies (62%), blinding of participants was assessed in 38 studies (66%), blinding of outcome assessment was assessed in 34 studies (59%), incomplete outcome data were assessed in 58 studies (100%), and selective outcome reporting was assessed in 56 studies (97%). Nineteen RCTs ( 24 , 26 , 27 , 32 , 33 , 37 , 41 , 45 , 53 , 54 , 56 , 58 61 , 64 , 67 , 73 , 81 ) were assessed to be of high quality ( Supplementary Figures 1 , 2 ). Bias risk of 5 CCTs ( 36 , 46 , 65 , 66 , 76 ) was assessed by NOS, and the number of stars was 7 from the study of Keles et al ( 36 ), 8 from the study of Riveros et al ( 46 ), 5 from the study of Jiang et al ( 65 ), 5 from the study of Long et al ( 66 ), and 8 from the study of Mason et al ( 76 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 5 were excluded for the following reasons: unpublished studies, [ 13 ] no available data on the outcome of interest in references, [ 14 , 15 ] non-English language, [ 16 ] and caudal anesthesia with lidocaine. [ 17 ] Finally, the remaining 12 studies [ 2 , 3 , 18 27 ] with existing data met our selection criteria and were included in the systematic review. Data of 5 studies, [ 18 , 20 , 21 , 24 , 25 ] which mainly involved in sedation score, was estimated from the median, range, and the size of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregated results were studied in 11 trials [ 2 , 3 , 18 24 , 26 , 27 ] and shown in Figure 3 . The results suggest that the time to first rescue pain medication in CA+dexmedetomidine group was significantly longer than in the CA group (WMD = 7.32, 95% CI: 5.74–8.91, P < .00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation